Research on Designing the Regenerative Braking System Apply to Conventional Vehicle - Duong, Tuan Tung; Do, Van Dung; Nguyen, Truong Thinh (Old Journal, 2019)
This study will calculate, design, and fabricate the inertial energy recovery model of the vehicle during braking or deceleration. This energy recovery unit is applied to conventional vehicles, including a double planetary gear set which is installed parallelly with the propeller shaft and a generator which is coaxial with the flywheel in order to convert the mechanical energy into electricity to recharge for the battery. The simulations and experimental models are built and controlled in the FTP75; NEDC; EUDC and ECR15 driving cycles. When the vehicle’s deceleration occurs, the energy recovery process will start. The control method for regenerative energy optimization is used for both simulation and experimental models. Experimental results show that the recovered energy is in the range of 22% to 38% of the inertial energy of the vehicle during the deceleration process. This energy is converted into electricity which will be used for additional loads on the vehicle.